2015
DOI: 10.1007/s11258-015-0508-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an invader on species diversity is stronger in the non-native range than in the native range

Abstract: We have yet to adequately quantify the impacts of invaders in their non-native ranges relative to their native ranges. Such biogeographical comparisons are crucial to better understand the role of invasive species in plant-plant interactions and in the evolution of community organization. Using Solidago canadensis, we conducted field surveys in the native range (North America) and non-native range (Europe) and correlated stem density and aboveground biomass of Solidago with associated plant species richness an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 57 publications
(63 reference statements)
2
28
0
Order By: Relevance
“…Considering such comparison, it is possible to denote the impact intensity. The application of this approach to terrestrial plant communities has indicated that invasive species may lead to reduced diversity in the introduced range in relation to native ranges (Hejda, ; Kaur et al, ; Ledger et al, ; Nielsen et al, ; Shah et al, ). In our study, the use of data from the native range of E. crassipes as a control enabled to demonstrate that these potential impacts are related to the invasion process and are not recorded in the native area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering such comparison, it is possible to denote the impact intensity. The application of this approach to terrestrial plant communities has indicated that invasive species may lead to reduced diversity in the introduced range in relation to native ranges (Hejda, ; Kaur et al, ; Ledger et al, ; Nielsen et al, ; Shah et al, ). In our study, the use of data from the native range of E. crassipes as a control enabled to demonstrate that these potential impacts are related to the invasion process and are not recorded in the native area.…”
Section: Discussionmentioning
confidence: 99%
“…This approach helps testing the frequently accepted (but poorly tested) hypothesis that introduced species promote greater impacts in the introduced range rather than the native one. There are indeed studies showing a more negative impact of invasive terrestrial plants on different aspects of diversity and assemblage composition in their introduced range rather than in their native one (Chen et al, ; Hejda, ; Ledger et al, ; Nielsen, Grøndahl, Callaway, Dickinson, & Ehlers, ; Taylor, Maxwell, Pauchard, Nuñez, & Rew, ). However, to the best of our knowledge, studies on highly invasive aquatic plants are yet to compare communities in native and introduced ranges.…”
Section: Introductionmentioning
confidence: 99%
“…, Ledger et al. ). Such community‐level impacts of native dominants can be comparable to those of invasive species (Hejda et al.…”
Section: Introductionmentioning
confidence: 99%
“…Nonnative species often show higher field performance in their nonnative than in their native ranges (Vil a et al 2011, Shah et al 2014, Ledger et al 2015, Davis et al 2018. This biogeographic phenomenon can be caused by altered abiotic conditions and biotic interactions in nonnative ranges (Mitchell et al 2006), such as release from specific antagonists present in the native range (Keane and Crawley 2002).…”
Section: Introductionmentioning
confidence: 99%